The effect of temperature and exposure time on the PH of beverages : a pilot study / Nur Nabila Abdul Wahab … [et al.] - Abdul Wahab, Nur Nabila; Rosman, Nur Afiqah; Venkiteswaran, Annapurny; Abu Bakar, Norashikin (2019)
The objective of this pilot study was to determine if temperature and exposure time affected the pH of various beverages. Methods: Five types of beverages (fruit drink, juice, carbonated drink, malted drink and sports drink) were selected for the pilot study. The pH of each drink was measured using separate cans at three different temperatures which are 4⁰C, 25⁰C and 27⁰C. The pH of the drinks were recorded in triplicate readings and repeated ANOVA test was done. Separately, each type of drink was assessed at an interval of 10 minutes for a total duration of 30 minutes. Triplicate readings were taken at a consistent room temperature of 27⁰C. A repeated ANOVA test was done to determine if there is any significant difference in pH changes caused by the time of exposure. Results: With the exception of juices, all other drinks showed significant difference in pH value when drinks are tested in different temperatures. As for the effect of exposure time on pH of beverage, three drinks (carbonated, sports drink and juice) showed significant difference. Conclusions: Given the fact that pH readings are different in the same drink in different environments, the timing of reading and the room temperature should be standardized for the main study. Further studies which include longer length of exposure time should be done to assess if there is any recognizable pattern of pH change in the various beverages.